Relationship of Nursing Service Quality with the Satisfaction Level of Participant Hypertension Patients BPJS at RSUD Dr. H. Soemarno Sosroatmodjo - Indrawijaya, I Ketut; Tasalim, Rian; Basit, Mohammad (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2022)
The quality of nursing services is one of the factors in the quality of health services which is one of the determining factors for the picture of health services in the community. Satisfaction is a feeling that comes as a result of the service action he receives, after the patient compares it with what he expects. To find out the relationship between the quality of nursing services and the level of satisfaction of patients with hypertension, BPJS participants at RSUD Dr. H. Soemarno Sosroatmodjo. This study uses an analytical survey research method with a cross sectional where each research subject is only observed once and measurements are made on the status of the character or variable of the subject on examination. The sample used was 30 people in the inpatient room at Dr. Hospital. H. Soemarno Sosroatmodjo. Sampling with total sampling technique. Data were analyzed using the Chi-square test. The quality of nursing services is mostly good as many as 16 people (53.3%), most of the respondents are satisfied as many as 18 people (60%), Chi-square test results obtained p value = 0.002. With a p value < (α = 0.05), it can be concluded that the hypothesis is accepted, which means that there is a relationship between the quality of nursing services and the level of satisfaction of hypertensive patients who are BPJS participants at RSUD Dr. H. Soemarno Sosroatmodjo. The conclusion, that there is a relationship between the qualities of nursing services with the level of satisfaction of patients with hypertension BPJS participants at RSUD Dr. H. Soemarno Sosroatmodjo.